Iris Nikolopoulou, The Greek capitalism through the prism of the 2009 economic crisis: institutional trajectory and accumulation regime - Iris Nikolopoulou (Revue de la Régulation)
This thesis argues that a comprehensive understanding of the 2009 Greek economic crisis requires to move beyond a purely financial analysis. A structural approach is essential to uncover the relationships, conflicts, and alliances among various actors and the evolving institutions shaped by these dynamics over time. The thesis explores the institutional specificities of the Greek accumulation regime from 1975 to 2022 through a historical, macro-institutional, and empirical lens. Using Regulation Theory as its analytical framework, it offers a new interpretation of the crisis, shedding light on its deep-rooted causes and socio-economic impacts.